The Work-life Balance Among Private Secondary School Teachers - Sabuero, Jimmy B. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The work-life balance emphasizes the relevance of behavioral and psychological development for public and commercial sector workers. It highlights how many workers lack the moral, emotional, and psychological stability for productive work and positive working relationships. It is advised that workers participate in work-life balance programs to help them manage their personal and professional lives. It is essential to comprehend the underlying causes of human attitudes and behaviors and the effects of managerial decisions and the organizational environment. Furthermore, the study used descriptive statistics with 50 faculty and staff through convenient sampling. The instruments also passed through validity and reliability testing. The study reveals that on the demographic profile, there were f=25, 50% of the employees were under probationary; also, it must have f=28, 56% under the tenure of 1-2 years in service to the organization; further, there were f=41; 82% with a salary of 10-20,000 Php, moreover, f=33 or 66% worked teacher. These figures revealed that most of them are establishing individuals. Furthermore, behavioral Management has an M=3.51; SD=.610 as interpreted as a very high work-life balance, while the emotional and psychological has an M=3.44; SD=.593 as interpreted as "very high work-life balance; while intellectual and survival have an M=3.56; SD=.501, as interpreted as "very high work-life balance; while vocational and spiritual with an M=3.48; SD=.583. Further reveals that the overall M=3.50; SD=.572 of work-life balance constitutes that faculty maintains personal and professional composure. Spillover theory proves that every professional has personal and professional boundaries that can influence their performance.